2012
DOI: 10.5712/rbmfc7(23)381
|View full text |Cite
|
Sign up to set email alerts
|

Depressão em Idosos de uma Comunidade assistida pela Estratégia de Saúde da Família em Passo Fundo, RS

Abstract: Objective: To identify the prevalence of depression in the elderly attended by the Family Health Strategy (FHS), and to identify the associated factors as well. Methods: transversal study with 151 elderly who live in the area registered in the FHS in Passo Fundo, RS. Data were collected through a structural questionnaire and Geriatric Depression Scale GDS-15. Results: 33.1% are male, aging predominantly from 60 to 69 years old, average schooling level 4.14 years of study (DP: 2.63), 8.2% are illiterate or semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
2
1
16

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 15 publications
(15 reference statements)
3
2
1
16
Order By: Relevance
“…Another study conducted in Passo Fundo, Rio Grande do Sul, by Borges and Dalmolin 29 , which evaluated 151 elderly persons receiving care through the Estratégia de Saúde da Família (the Family Health Strategy), using the same data collection instrument, the GDS, found that 18.0% had mild depression and 3.3% had severe depression, values greater than those of the present study. Casagrande et al 16 assessed a group of elderly persons and found that only 12.0% of respondents had symptoms of depression.…”
Section: Discussioncontrasting
confidence: 55%
“…Another study conducted in Passo Fundo, Rio Grande do Sul, by Borges and Dalmolin 29 , which evaluated 151 elderly persons receiving care through the Estratégia de Saúde da Família (the Family Health Strategy), using the same data collection instrument, the GDS, found that 18.0% had mild depression and 3.3% had severe depression, values greater than those of the present study. Casagrande et al 16 assessed a group of elderly persons and found that only 12.0% of respondents had symptoms of depression.…”
Section: Discussioncontrasting
confidence: 55%
“…Este método fatorial reduziu a dimensionalidade dos itens e destacou aqueles mais representativos e correlacionados, que foram: medo de momentos futuros, anedonia que compromete a capacidade de sentir prazer na vida, ansiedade e condição apática ligada ao isolamento social. Esses itens são semelhantes aos encontrados na literatura consultada [11,13,24], apontando que tais condições são determinantes para o risco depressivo, como observado o item 2 da escala: "diminuiu parte de suas atividades de interesse", que obteve maior pontuação na matriz de comunalidade, sugerindo forte influência para deflagrar o risco de depressão.…”
Section: Discussionunclassified
“…Conhecer as condições de saúde dos idosos revestese de grande importância científica e social, visto que esses transtornos afetam a capacidade funcional, apresentam elevada frequência e comprometem negativamente a qualidade de vida dos indivíduos [13]. O uso sistemático de escalas validadas, de boa confiabilidade avaliativa sobre a depressão, pode viabilizar a detecção precoce desse distúrbio na prática clínica e assistencial.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…A study carried out with elderly patients in Passo Fundo city, Rio Grande do Sul State, Brazil, found that 66.9% of them reported having hypertension, demonstrating its high occurrence among the elderly. 18 A study conducted with elderly residents in rural areas found that elderly patients with a greater number of morbidities were 24% more likely to have indicative depression, but it had no relationship to hypertension and diabetes.…”
mentioning
confidence: 99%